A new swelling - creep model for red-bed mudstone and its application - Hongyi Yan; Feng Yu; Chaobo Zhu; Jianwei Yuan; Qiang Wang; Jiang Wu (Frontiers in Earth Science)
In the red-bed region, engineering structures often encounter safety risks due to the swelling and creep properties of mudstone. Presently, there is a deficiency in constitutive equations capable of characterizing mudstone behavior under combined stress and swelling. To tackle this challenge, the deformation characteristics of red-bed mudstone were summarized based on the previous experimental data. A new element combination model (namely, swelling-creep model), comprising a Burgers body, swelling body, and nonlinear damper, was established to describe attenuated creep, swelling deformation, and accelerated creep, respectively. Based on this, the three-dimensional constitutive equations of the swelling-creep model were derived. Subsequently, based on the UDM program of FLAC3D, the model was further developed using C++ language. Additionally, the developed swelling-creep model was validated through the numerical simulation experiments. Finally, the swelling-creep deformation process of red-bed mudstone under tensile stress conditions was simulated using the developed swelling-creep model. The research results indicate that the fitting results of the swelling-creep model are in good agreement with the experimental data, demonstrating its accuracy in describing the swelling and creep characteristics of red-bed mudstone. Moreover, when red-bed mudstone is subjected to axial tensile stress, the swelling effect significantly increases the axial strain rate and accelerates the transition to the accelerated creep stage.